Effect Of Fiber Loading And Silane Treatment On Properties Of Poly (Butylene Adipate -Co- terephthalate)/ Oil Palm Empty Fruit Bunch Fiber Biocomposites - Nozari, Zahra (2010)

(untitled)
In this study, green composites of oil palm empty fruit bunch (OPEFB) fiber (100-200 μm ) with poly(butylene adipate-co-terephthalate) (PBAT) using vinyl tris (2-methoxyethoxy)silane as crosslinking agent were prepared by melt blending technique. The effect of fiber loading and addition of vinyl tris (2- methoxyethoxy)silane on the mechanical and thermal properties of PBAT/OPEFB biocomposites were investigated. The composites were prepared by using 10, 20, 30, 40 and 50 % by weight of fiber. Different fiber loadings were tested to determine the optimum amount of OPEFB required producing good composite. Consequently, the composite with 40% fiber loading, blending temperature and time of 120 ºC and 12 minutes, respectively and rotation speed of 30 rpm were found as the best formulation and condition for preparation of the composite.Mechanical properties of the composite were assessed by tensile, flexural and impact strength (notched and unnotched). In addition, water absorption and degradation study were also carried out. The composites showed the increase in tensile strength and modulus, flexural strength and modulus, unnotched and notched impact strength with the increment of fiber loading. The presence of silane led to increase in tensile properties, flexural strength, unnotched and notched impact strength but reduction in flexural modulus. The composite with 4% silane loading showed the best mechanical and physical properties. FTIR spectra of the composites indicated that there were interaction between the components of the composites and new bonds formed after addition of additive. Thermal stability of the composites decreases with increasing of fiber content. The presence of silane on the composites did not show any significant improvement in thermal stability as shown by Thermogravimetric Analysis. The SEM micrographs of the fractured surfaces gave clear indication of the effect of silane in reduction of void size and close interaction of PBAT and OPEFB fiber was clearly demonstrated for composite with additive which resulted in improvement of mechanical properties of composite. Dynamic mechanical analysis results showed that storage modulus and loss modulus of composites increased with increasing fiber loading. Furthermore, Tg of PBAT positively shifted after the addition of fiber, indicated there is interaction between PBAT and OPEFB. The crosslinked composite presented higher Tg than non crosslinked composite. With the increased of fiber loading, the water absorption was also increased, and the addition of additive led to less water absorption. The biodegradability of composites was evaluated by the soil burial test for three months. The results showed that the composites were degraded faster than pure matrix due to cellulosic materials is easily attacked by microorganisms. It was also observed that addition of silane as well as the fiber loading tends to promote the degradation rate of PBAT. However the rate of biodegradation of PBAT was slower than expected.